A new species of Austrophasiopsis Townsend (Diptera: Tachinidae) from Nepal, with systematic notes on the genus - Shima, Hiroshi; Tachi, Takuji (Zootaxa, 2022)
A new species of Austrophasiopsis Townsend from Nepal, Austrophasiopsis caliginosa sp. nov., is described and illustrated. Two known species, A. formosensis Townsend and A. luteipennis Mesnil, are redescribed and illustrated and a key to the three species is provided. Based on a morphological study, Austrophasiopsis is moved from its current position in the tribe Minthoini to the Leskiini (Tachininae) where it is considered close to Solieria Robineau-Desvoidy.